2009
DOI: 10.1038/sj.bdj.2009.559
|View full text |Cite
|
Sign up to set email alerts
|

Numbness of the ear following inferior alveolar nerve block: the forgotten complication

Abstract: movement and appearance is affected when the CN V and VII are affected. 10,11 The following case reports of a distant complication that affects the auriculotemporal nerve after the administration of local anaesthetic using standard inferior alveolar nerve block technique. CASE REPORTA 30-year-old medically-fit Chinese female was given an appointment to have her mandibular left wisdom tooth removed under local anaesthesia after experiencing pericoronitis. She had experienced having her deciduous teeth removed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Firstly, it is particularly important to predict the variability of ATN anatomy in the field of surgery involving the infratemporal fossa and dental anesthesia. Specifiaclly, correct recognition of these structures could prove highly advantageous in the surgical field [ 19 25 ] as well as demystifying possible side effects that occur during administration of local anesthesia to IAN [ 26 27 ]. Secondly, awareness of ATN anatomy seems to be particularly useful in understanding and explaining the mechanism of neuralgia [ 28 30 ] and migraine headaches [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it is particularly important to predict the variability of ATN anatomy in the field of surgery involving the infratemporal fossa and dental anesthesia. Specifiaclly, correct recognition of these structures could prove highly advantageous in the surgical field [ 19 25 ] as well as demystifying possible side effects that occur during administration of local anesthesia to IAN [ 26 27 ]. Secondly, awareness of ATN anatomy seems to be particularly useful in understanding and explaining the mechanism of neuralgia [ 28 30 ] and migraine headaches [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same can be considered to explain the pain felt along the distribution of any of these branches without a reason as suggested by Siessere et al (2009). This may explain the temporary numbness of external ear and the region supplied by ATN as reported after IAN block by Ngeow & Chai (2009). It can explain the incomplete nerve block in dental anaesthesia or inadvertent effect on inltrating the local anaesthetic drug.…”
Section: Discussionmentioning
confidence: 93%
“…The phenomenon may be an anatomic and phylogenetic result of the highly variable and complicated branching pattern and forms of communications among periotic cutaneous sensory nerves distribution. Anatomically, the great auricular nerve was found to essentially connect with the parotid gland, mostly located inferior to the auricle or in the postauricular region, whereas the auriculotemporal nerve trunk provided more innervation to the skin of the upper half of the pinna and the anterior half of the external auditory meatus . Ryan and Fee found that the impairment of the great auricular nerve, demonstrated by the results of the sensory testing, was able to induce periotic sensory symptoms, particularly numbness, during parotidectomy .…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically, the great auricular nerve was found to essentially connect with the parotid gland, mostly located inferior to the auricle or in the postauricular region, whereas the auriculotemporal nerve trunk provided more innervation to the skin of the upper half of the pinna and the anterior half of the external auditory meatus. 9,[12][13][14][15] Ryan and Fee found that the impairment of the great auricular nerve, demonstrated by the results of the sensory testing, was able to induce periotic sensory symptoms, particularly numbness, during parotidectomy. 6 And the study by Schmidt et al reported that the auriculotemporal nerve produced numbness, pain, or both in the temporomandibular joint region.…”
Section: Discussionmentioning
confidence: 99%